A Local history of Greek polytheism : gods, people, and the land of Aigina, 800-400 bce - Polinskai︠a︡, I. (Religions in the Graeco-Roman World, 2013)
This book provides the first comprehensive and detailed study of the deities and cults of the important Greek island-state of Aigina from the Geometric to Classical periods (800-400 BCE). It rests on a thorough first-hand reconsideration of the archaeological, epigraphic and literary evidence. The development of the local cults is reconstructed, along with their interrelationships and how they responded to the social needs of the Aiginetans. Revising other recent models of interpretation, the author proposes a distinctive approach, informed by anthropology and social theory, to the study of the religious life of the ancient Greeks. On this basis, she uses the case of Aigina to explore fundamental issues such as the nature and variety of local religious worlds and their relationship to the panhellenic concepts and practices of Greek religion.